THE QUR'ANIC PERSPECTIVE ON DISASTER SEMIOTICS - Mardan Mardan (Jurnal Adabiyah: Humanities and Islamic Studies, 2018)
This research entitled The Qur'anic Perspective on Disaster Semiotics. It uses interpretive approach with the method of tafsīr maudū'ī" and comprehensive semantic analysis. The object of this research is The Qur'an verses concerning with disasters. The results indicate that the disaster semiotics in the Qur'an, include the following terms: al-balā', al-musībah, al-fitnah, and al-‘azāb. From these words, several facts are obtained: (1) disaster as a test is a necessity of life for mukallaf humans, which is carried out by God himself without the involvement tried in determining the way, time, and form of the disaster; (2) a disaster, which is a necessity of life including spaciousness and life suffering, whose levels are in accordance with the level of one's faith, the higher experience disasters more severe than others; (3) the disaster in the form of God's gift or favor cannot be used as evidence of divine affection as suffering does not always mean His wrath; (4) disasters come, in addition to natural factors, also because of human sins. If that also happens, humans must respond to the disaster as education and divine enlightenment, as a blessing to believers, and a warning to sinners and punishment for those who are unjust and overreach.